Increased Survival After Cecal Ligation and Puncture in Mice Delivering Interleukin 12: The Role of TH1 and TH2 cells - Kiran, Bayram; Zeybek, Ümit; Turna, Akif; Durmaz, Hayati; Cabioglu, Neslihan; Deniz, Günnur (Archives of Clinical and Biomedical Research, 2025)
Introduction: Severe injury is associated with depressed immune response. The purpose of this study was to analyze the role of TH1 and TH2 cells in the stimulated peripheral blood mononuclear cells and determine the effect of IL-12, a cytokine stimulating TH1 cell proliferation, when administered to septic mice. Methods: Male Balb/c mice underwent sham operation (group 1) or bacterial peritonitis (group 2) which was induced by cecal ligation and puncture and they were treated with IL-12 (group 3), or with IL-10 (group 4) or with both cytokines intraperitoneally (group 5). The T helper-1 (TH1) and T helper-2 (TH2) cells were analyzed following stimulation of peripheral blood mononuclear cells with poly-myristate-acetate (PMA) by measuring the intracytoplasmic expression of interleukin-4 (IL-4) and interferon-γ in CD3+- lymphocytes with flow-cytometry. The survival rates of treated mice were compared with non-treated mice. Results: The number of TH1-cells in mice with peritonitis (group 2) was significantly lower than those in sham-operated mice (p=0.03). In contrast, the number of TH2-cells was found to be higher in mice with peritonitis (p=0.001) compared to sham-operated. IL-12-administration restored the number of TH1 and TH2 cells to those of sham-operated ones. The survival rate of mice treated by IL-12 was found to be significantly improved compared to non-treated mice (p=0.002). However, IL-10 injection almost neutralized the restoring effect of IL-12 administration by improving the survival rate and the TH1/TH2 cell counts. Moreover, IL-10 administration alone resulted in lower survival than that of control and sham-operated group (p=0.002). Conclusions: Changes in the TH1 and TH2 cells and/or cytokine balance in peritonitis in mice might induce a shift toward a TH2 dominant phenotype. Therapies designed to increase the number of TH1 cells such as IL-12 adminisration might be beneficial in the treatment of severe sepsis after peritonitis whereas IL-10 has a deleterious role in sepsis.